Characterization of the initial ontogeny of Leiarius marmoratus (GILL, 1870): larvae to juvenile - Coelho, Geovanna Carla Zacheo [UNESP]; da Silva Costa, Raphael [UNESP]; Bashiyo-Silva, Cristiane [UNESP]; Silva de Souza, Fabrício Marçal [UNESP]; de Castro Ribeiro, Douglas [UNESP]; Augusto Senhorini, José; Verissimo-Silveira, Rosicleire [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (Hindawi, 2019)
Aiming to provide data on the biology of Leiarius marmoratus, which will aid in its production in captivity, as well as in studies for its preservation in the environment, this work had as objectives: analyze and describe main morphological alterations during larval ontogeny of the species. We analyzed 205 individuals, obtained by induced reproduction (Colpani Pisciculture) and kept in CEPTA/ICMBIO, Pirassununga, São Paulo, Brazil. Analyses were performed from hatching moment to 30th day. The specimens were classified into two periods: larval (Stages: vitelline, pre-flexion, flexion, post-flexion) and juvenile. Hatched larvae showed ident chromatophores only at anterior and posterior extremities of yolk sac. The standard length ranged from 2.16 mm (yolk) to 28.84 mm (Youth). Dorsal fin rays were initially observed at flexion stage (12–14 rays). Major alterations occurred during post-flexion/juvenile stage, when dorsal, pectoral, pelvic, anal, and caudal fins were observed and pigmentation intensified throughout the lateral region, forming bands in the body, one between the end of the head and beginning of dorsal to pelvic fin, and another one beginning at dorsal to caudal peduncle and four longitudinal at the head.
Keywords: initial development; larvae; morphology; ontogeny; siluriform